EKOTEOLOGI DALAM PEMIKIRAN BADIUZZAMAN SAID NURSI - Ridwanuddin, Parid (LENTERA, 2017)
Eco-theology (theology of environment) is an area of study regarding the interrelation between theological-philosophical thoughts within religious teachings and the environment. Hence, within this area, discourse on theology is not limited only to merely theological dimensions but also ecological dimensions of God/s. Theologically speaking, crises of environment that is happening today relates to views and behaviours of humankind that, consciously of non-consciously, that may alter the balance of earth ecosystem. This paper aims at investigating the theology of environment proposed by Badi’uzzaman Said Nursi. According to Nursi, the nature is a tajalli, a manifestation of God’s existence and a representation of His many names. In the same time, the nature is the clearest evidence of God’s existence and Humanity is His caliphate and His Manifestation.